Development Of An Autonomous 3 KW Inverter For Solar And Wind Mini Power Plants - B.E. Egamberdiev; H.H.Mamirov (Zien Journals, 2025)
The paper presents the results of the development of a 3 kW inverter design for solar and wind mini power plants used for the national economy and industry, as well as the design and manufacture of a pilot batch of solar inverters designed for use as part of photovoltaic or wind power plants.
Keywords: construction; inverter; mini solar and wind power plant; power